A Review on the Pharmacological Activities and Phytochemicals of Alpinia officinarum (Galangal) Extracts Derived from Bioassay‑Guided Fractionation and Isolation - Basri, Aida Maryam; Taha, Hussein; Ahmad, Norhayati (Pharmacognosy Reviews)
The rhizomes of Alpinia officinarum Hance have been used conventionally for the treatment of various ailments, triggering a wide interest from the scientific research community on this ethnomedicinal plant. This review summarizes the phytochemical and pharmacological properties of the extracts and fractions from A. officinarum, a plant species of the Zingiberaceae family. Different parts of the plant – leaves, roots, rhizomes, and aerial parts – have been extracted in various solvents – methanol, ethanol, ethyl acetate, hexane, dichloromethane, aqueous, chloroform, and petroleum ether, using various techniques – Soxhlet extraction, maceration, ultrasonication, and soaking, whereas fractionation of the plant extracts involves the solvent–solvent partition method. The extracts, fractions, and isolated compounds have been studied for their biological activities – antioxidant, antibacterial, anti‑inflammatory, anticancer, antiproliferative, inhibition of enzymes, as well as the inhibition of nitric oxide production. More findings on A. officinarum are certainly important to further develop potential bioactive drug compounds.
Keywords: Alpinia officinarum; ethnomedicinal plant; lesser galangal; pharmacological; phytochemicals; Zingiberaceae